KEGIATAN BERKELANJUTAN PEMBINAAN KESADARAN HUKUM DAN PEMBERDAYAAN DIRI MASYARAKAT DALAM PERSPEKTIF PENTINGNYA BERAKHLAK MULIA DI POLRES METRO JAKARTA UTARA - Mumpuni, Sri; Maria, Kiki; Istiqomah, Istiqomah; Tarmudi, Tarmudi (Lembaga Pendidikan dan Penelitian Manggala Institute, 2025)
In relation to the role and purpose of community service, especially for prisoners at the North Jakarta Metro Police as mentioned above, there is an interesting phenomenon that has been implemented by a team of lecturers from Bung Karno University Jakarta by formally organizing a Community Service program in the prisoners' meeting room with the theme